Epithelial Cells Attenuate Toll-Like Receptor-Mediated Inflammatory Responses in Monocyte-Derived Macrophage-Like Cells to Mycobacterium tuberculosis by Modulating the PI3K/Akt/mTOR Signaling Pathway - Yang, Yi; Sun, Yingfei; Xu, Jinrui; Bao, Kangda; Luo, Meihui; Liu, Xiaoming; Wang, Yujiong (Mediators of Inflammation, 2018)
Both alveolar macrophages (AMs) and alveolar epithelial cells (AECs) are main targets of Mycobacterium tuberculosis (M. tuberculosis (Mtb)). Intercellular communications between mucosal AECs and AMs have important implications in cellular responses to exogenous insults. However, molecular mechanisms underpinning interactions responding to Mtb remain largely unknown. In this study, impacts of AECs on Toll-like receptor- (TLR-) mediated inflammatory responses of AMs to Mtb virulent strain H37Rv were interrogated using an air-liquid interface (ALI) coculture model of epithelial A549 cells and U937 monocyte-derived macrophage-like cells. Results showed that Mtb-activated TLR-mediated inflammatory responses in U937 cells were significantly alleviated when A549 cells were coinfected with H37Rv, in comparison with the infection of U937 cells alone. Mechanistically, PI3K/Akt/mTOR signaling was involved in the epithelial cell-modulated Mtb-activated TLR signaling. The epithelial cell-attenuated TLR signaling in U937s could be reversed by PI3K inhibitor LY294002 and mTOR inhibitor rapamycin, but not glycogen synthase kinase 3β inhibitor LiCl, suggesting that the epithelially modulated-TLR signaling in macrophages was in part caused by inhibiting the TLR-triggered PI3K/Akt/mTOR signaling pathway. Together, this study demonstrates that mucosal AEC-derived signals play an important role in modulating inflammatory responses of AMs to Mtb, which thus also offers an insight into cellular communications between AECs and AMs to Mtb infections.